Correction: Abbas et al. Bioactive Compounds, Antioxidant, Anti-Inflammatory, Anti-Cancer, and Toxicity Assessment of Tribulus terrestris-In Vitro and In Vivo Studies. Antioxidants 2022, 11, 1160 - Malik Waseem Abbas; Mazhar Hussain; Saeed Akhtar; Tariq Ismail; Muhammad Qamar; Zahid Shafiq; Tuba Esatbeyoglu (MDPI AG, 2024)
In the original publication [...]